Economic, social, cultural and environmental rights and transitional justice: a cultural analysis of law perspective on the case of the Plan de Sánchez Massacre - Cardoso Campos, Bárbara Pincowsca; García Arboleda, Juan Felipe (Universidad Hemisferios, 2025)
This article explores the intersection between economic, social, cultural, and environmental rights (ESCR) and transitional justice (TJ) in the Inter-American system, using the Plan de Sánchez Massacre v. Guatemala (2004) case as a pivotal moment in the emergence of this legal doctrine. The ruling issued by the Inter-American Court of Human Rights (IACtHR) not only acknowledged the gravity of the human rights violations committed by state security forces but also set a precedent for expanding reparations beyond traditional civil and political rights. By incorporating ESCR considerations, the court strengthened the link between TJ and structural inequalities, particularly regarding historically marginalized groups like the Maya indigenous people. Framed within Paul W. Kahn's cultural analysis of law (CAL), this study argues that Plan de Sánchez case represents a natal judgment in the legal doctrine of ESCR and TJ, emphasizing how the categories and legal narratives used by the Inter-American judges shape and give meaning to the legal culture surrounding justice, state responsibility, and reparations. By articulating the connection between ESCR and TJ, this article highlights the potential for a more holistic legal culture within the Inter-American system, one that not only provides redress for past atrocities but also fosters long-term social transformation through rights-based reparations.